Pharmaceutical Biocatalysis : Fundamentals, Enzyme Inhibitors, and Enzymes in Health and Diseases - Grunwald, Peter (Singapore : Jenny Stanford Publishing, 2019)
This book provides an overview of the world market of therapeutic enzymes and enzyme inhibitors, rare diseases, orphan drugs, the costs of drug development and therapies, and enzymes in downstream processing of pharmaceuticals. It discusses carbonic anhydrase inhibitors and their multiple drug interactions, carboxylesterase inhibitors for pharmaceutical applications, employment of inhibitors for the treatment of neurodegenerative diseases, use of engineered proteins, bioactive peptides, and fibrinolytic enzymes for thrombolytic therapy, and enzymes important for the design and development of new drugs/drug metabolites such as aldehyde oxidases and cytochrome P450 enzymes and the role the latter play in vascular biology and pathophysiology. The treatment of cancer is explored in connection with enzymatic amino acid deprivation therapies and new drugs that act as chemical degraders of oncogenic proteins. The book also introduces the resistance mechanisms of cancer. Furthermore, it provides an insight into the relationship between pathological conditions of cardiovascular disease and oxidative stress. The text also focuses on the potential use of nanoparticles as carriers for enzymes with medical relevance, computer-aided drug design for the identification of multi-target directed ligands, and the development of improved therapeutics through a glycan-designer approach. It concludes with an introduction to the chemoenzymatic synthesis of drugs.
OCLC-licensed vendor bibliographic record.
Keywords: Enzymes -- Industrial applications; Pharmaceutical biotechnology; MEDICAL / Biotechnology; MEDICAL / Clinical Medicine; MEDICAL / Pharmacology